Straight eye for the queer ad: attitudes, skepticism, inferences of manipulative intent and willingness to buy. Issue 5 (11th November 2020) - Cheah, Isaac; Teah, Min; Lee, Sean; Davies, Zachary
Abstract : Purpose: This study aims to provide a conceptual framework to investigate the effects of consumer attitudes toward brands and attitudes toward a series of fashion oriented print advertisements with and without homosexual themes, on consumer willingness to buy from brands. The influence of consumer skepticism and inferences of manipulative intent (IMI) as moderators between these variables is also investigated. This study also closes various research gaps identified within the literature. Design/methodology/approach: A self-administered survey instrument was designed using established scales to collect data through an online questionnaire. Fashion advertisements namely one advertisement representing homosexual content and one heterosexual advertisement were used in the study within subjects (e.g. male and female) design. Statistical techniques, specifically factor analysis, regressions and multiple regressions are used to analyze the data. Findings: The findings indicate significant and positive relationships between attitude toward the brand and advertisement as well as willingness to buy for both males and females. The moderation analyses noted that consumer skepticism enhanced the relationship between attitude toward the brand and attitude toward the advertisement, but weakened the relationship between attitude toward the advertisement and willingness to buy, only for the female cohort. Similarly, a weakening effect of IMI was noted on the relationship between attitude toward the advertisement and willingness to buy. Research limitations/implications: The current study contributes to the literature on homosexual imagery in advertising. In applying the persuasion knowledge model, the current study demonstrates the applicability of the model to homosexual themes in fashion advertising while accounting for the effects of consumer skepticism and IMI. Practical implications: The current research highlights the importance of accounting for gender differences when introducing homosexual themes in fashion advertisements. Heterosexual males and females differ in their attitudes toward homosexual themes in fashion advertising, as well as how skeptical they are with regards to the motives of the advertiser. While a great deal of acceptance is already present in today's society, these differences still need to be accounted for in future fashion advertising campaigns. Originality/value: The present study represents an examination of consumer responses to a series of fashion advertisements in Australia and provides useful implications to marketers of fashion products. The study further contributes to the literature on consumer skepticism and IMI with regards to cause-related advertising.